Applying Ecological Systems and Micro-Tipping Point Theory for Understanding Tourists' Leisure Destination Behavior - Woodside, Arch; Martin, D. (SAGE Publications Inc, 2008)
Micro-tipping point (MTP) theory includes the proposal that a specific stream of unconscious and conscious thoughts result in a go and no-go discretionary action in a given context (e.g., whether or not to visit a given destination in a given season or year, with particular persons being included or excluded from the trip). The specific stream represents a stream or conjunctive combination of thoughts in context that results in a tourist party actually taking the steps that include booking the trip and experiencing a destination firsthand. Building such contingency models that are applicable to real-life combinations of unconscious and conscious thinking requires collecting data from informants on both implicit and explicit beliefs, attitudes, and thinking rules relevant for a specific yes or no context. This article illustrates applying the long interview for collecting such data and using quantitative comparative analysis for constructing MTP models.